Pemberdayaan Masyarakat Melalui Budidaya Ikan Lele Bioflok Kampung Rentan Narkoba di Gampong Mon Geudong Kecamatan Banda Sakti Kota Lhokseumawe - Risna Dewi; Dwi Fitri; Maisyura Maisyura; Nada Nabila; Makmur Butar-Butar; Zakiah Nasution (Universitas Teuku Umar, 2022)
The community service program of the Malikussaleh University 2021 with a study in the drug-prone village of Gampong Mon Geudong, Banda Sakti District, Lhokseumawe City. PemudaGampong Mon Geudong (PGM) Bersinar is a partner who runs a catfish farming program with a biofloc system. In its management, partners experience limited mastery of biofloc system catfish farming techniques, product marketing, and community vulnerability to drug abuse. To overcome this problem, solutions will be offered for partners in overcoming problems faced by partners which we will package in the form of meetings with partners and related parties. These solutions are to provide knowledge for catfish farming with a biofloc system. Solutions by carrying out Focus Group Discussions (FGD) for community empowerment through catfish farming with a biofloc system, so that they can discuss and identify problems and solutions for the solution for the stage of community empowerment through awareness, capacity building and empowerment for the next stage of making an independent and free economy from the dangers of drugs.